2010
DOI: 10.1590/s0073-47212010000400020
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive characteristics of characid fish species (Teleostei, Characiformes) and their relationship with body size and phylogeny

Abstract: ABSTRACT. In this study, I investigated the reproductive biology of fish species from the family Characidae of the order Characiformes. I also investigated the relationship between reproductive biology and body weight and interpreted this relationship in a phylogenetic context. The results of the present study contribute to the understanding of the evolution of the reproductive strategies present in the species of this family. Most larger characid species and other characiforms exhibit a reproductive pattern t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0
12

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 21 publications
3
24
0
12
Order By: Relevance
“…Although reproductive period seems to start in August in the downstream site, the reproductive peak occurred in spring and summer for all sites. These results corroborate studies conducted for other Characidium species, as well as for most species of Characiformes for which data are available (Vazzoler & Menezes, 1992;Braga, 2006;Azevedo, 2010). Another study conducted in the Maquiné river, Rio Grande do Sul, involving other populations of C. pterostictum, also reported similar results regarding reproductive period (Becker et al, 2008).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Although reproductive period seems to start in August in the downstream site, the reproductive peak occurred in spring and summer for all sites. These results corroborate studies conducted for other Characidium species, as well as for most species of Characiformes for which data are available (Vazzoler & Menezes, 1992;Braga, 2006;Azevedo, 2010). Another study conducted in the Maquiné river, Rio Grande do Sul, involving other populations of C. pterostictum, also reported similar results regarding reproductive period (Becker et al, 2008).…”
Section: Discussionsupporting
confidence: 88%
“…Studies in temperate regions show a positive correlation between the change in water temperature and photoperiod with GSI for several teleost species (Azevedo et al, 2000;Lampert et al, 2007;Azevedo, 2010). In our study, a positive correlation between photoperiod and GSI was found only for the downstream site.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…For the later developmental stages of vertebrate embryos, numerous available data show that specific differences are the result of allometric growth and/ or heterochrony (Gould, 1977;Raff and Wray, 1989;Mckinney and Mcnamara, 1991;Gould, 1992;Duboule, 1994;Smith, 2001;Azevedo, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Esse é um dos fatores abióticos que modulam as táticas reprodutivas de muitas espécies (Vazzoler, 1996) e também relatado em outros estudos realizados nas regiões subtropical ou temperada no sul do Brasil (azeVeDo et al, 2000; gonçalVes et al, 2005;Muniz et al, 2008;giora & fialho, 2009;azeVeDo, 2010 (2010) é comum a muitas espécies de peixes e provavelmente está relacionado às diferenças entre machos e fêmeas no que se refere ao processo de acúmulo de material de reserva nos gametas pois, como o gasto energético na produção de espermatozoides é menor, o macho pode produzi-los antes e estar sempre pronto para a fecundação.…”
Section: Discussionunclassified